Multi-objective Optimization Analysis of Gear Shaft - Zhong Zifeng; Nie Peng (Jixie chuandong, 2015)
For the problem of gear shaft resonance,the gear shaft is analyzed with adopting finite element method,the inherent frequency and vibration mode are obtained.The maximum of first and second inherent frequency and the minimum quality are set as objective function,based on Isight integrated optimization platform,the AMGA,NCGA,NSGA-II is adopted to the optimization design in respect of the diameter of neck of shaft.After optimization,the first inherent frequency and second inherent frequency are improved by 6.16% and 6.13%.The low inherent frequency are outside the range of excitation frequency,the quality of gear shaft is reduced,so the resonance will be effectively avoided.